Assessment of groundwater quality and irrigation suitability in the Doodhganga Catchment, Kashmir Valley - KHAN, TANZEEL; KUMAR, ROHITASHW; KRISHAN, GOPAL; KHAN, J.N.; AHMAD, LATIEF; BANDAY, NEELOFAR; KHAN, IMRAN (Journal of Soil and Water Conservation, 2025)
This study evaluates groundwater quality in the Doodhganga catchment area, located in the Kashmir Valley, for its suitability for agricultural use. A comprehensive analysis of 66 groundwater samples collected over two years (2022–2023) assessed physico-chemical parameters, including pH, Electrical Conductivity (EC), Total Dissolved Solids (TDS), hardness, and concentrations of major ions like calcium (Ca²+ ), magnesium (Mg²+), chloride (Cl–), and bicarbonate (HCO3–). Results indicated that groundwater falls within the “fresh water” category, adhering to both WHO and ISI standards, ensuring suitability for agriculture irrigation. Key indices such as Residual Sodium Carbonate (RSC), Kelley’s Index (KI), and Permeability Index (PI) were calculated to assess irrigation quality. The findings underscore the groundwater’s general potability and suitability for irrigation, with minor hardness concerns, linked to geological formations, which may affect industrial applications. This study supports sustainable groundwater management in the Kashmir Valley, vital for agricultural productivity and water security.